Pengaruh Ukuran Perusahaan, Audit Tenure, dan Profitabilitas Terhadap Audit Delay pada Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Heny Nur Aini; Purwantoro Purwantoro; Imang Dapit Pamungkas; Hermawan Triono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of company size, tenure audit, and profitability on audit delay in insurance companies listed on the Indonesia Stock Exchange for the 2020–2024 period. Audit delays are a crucial issue because they have implications for the relevance of information and stakeholder decision-making. The study uses a quantitative approach with a causal associative design, utilizing secondary data from audited financial statements selected through purposive sampling. Data analysis used multiple linear regression with SPSS version 25. The results showed that simultaneously, the three variables had a significant effect on the audit delay with an F value of 3.282 (sig. 0.025) and an R² of 11.5%. Partially, only the size of the company had a significant positive effect, indicating that large-scale companies require longer audit times due to operational complexity and high transaction volumes. Audit tenure and profitability had no significant effect, suggesting that the duration of the auditor's engagement and the level of the company's profits were not the main determinants of the timeliness of audits in the insurance industry. The findings show that company size has a greater influence compared to auditing tenure and profitability.